Dynamics of land use in a rural settlement in the Brazilian Legal Amazon - Duarte, Miqueias Lima [UNESP]; Sousa, Jocy Ana Paixao de [UNESP]; Castro, Amazonino Lemos de [UNESP]; Lourenco, Roberto Wagner [UNESP] (Associacao Brasileira De Engenharia Sanitaria E Ambiental, 2021)
Deforestation in the Amazon has reached alarming numbers in recent decades. The main factors causing this issue are not only large and medium-sized farmers, land grabbing, and illegal mining but also agrarian reform settlements, which may be contributing to the increase in deforestation rates. In this context, this study aims to evaluate the dynamics of land use in the rural settlement Santo Antonio do Matupi, located in the south of the State of Amazonas. This time-series study analyzed changes in land use and land cover from 1992 to 2018 using supervised classification techniques. In this scenario, simulations were carried out of the dynamics of land use for the period between 2028 and 2038 using the cellular automaton method of Markov (CA-MARKOV). The results show that, in the studied period, the greatest losses were in primary forests and that the most critical period of deforestation rates recorded was from 2004 to 2018 when 63.28% of the area was converted into pastures. Future scenarios based on the period studied indicate losses of up to 5.26% of areas occupied by forests by 2028, and a further 5.60% by 2038, exceeding 80% of the total area deforested in the settlement. This study demonstrates that the current model of land use and occupation practiced in the settlement is unsustainable and that future scenarios are worrying. This situation highlights a need to effectively implement programs that aim a sustainable rural development in the settlement, in addition to monitoring and controlling deforestation, designed for current managers and other sectors of the society concerned with the conservation and preservation of forests.
Keywords: Amazon biome; agrarian reform; deforestation; CA-Markov model